Study on fiber hybridization effect of engineered cementitious composites with low- and high-modulus polymeric fibers. (1st June 2016) - Pakravan, Hamid Reza; Jamshidi, Masoud; Latifi, Masoud
Graphical abstract: Highlights: Improving the ductility of ECC composite with hybrid fibers. Study of low and high modulus polymeric fibers in hybrid composite. Study of the effect of fiber cross-sectional shape on the flexural behavior of hybrid ECC composite. Hybridization of PP fibers with different cross-sectional shape and PVA fiber in ECC composite. Abstract: In this study the flexural and compressive properties of hybrid engineered cementitious composite (ECC) was investigated. The hybridization with low- and high-modulus fibers was employed to increase deformability and flexural strain capacity of the ECC composite. It was found that the hybridization with non-round polypropylene (PP) fiber and low modulus polyvinyl alcohol (PVA) fiber have remarkable effect on the improving strain-capacity of resultant composite. The strain-capacity of hybrid ECC was increased by replacement of 20 vol.% of triangular PP fiber and low modulus PVA fiber up to 33% and 148%, respectively. This hybridization also increased the toughness ratio and meets the requirements for the strain-hardening with multiple cracking behaviors of cementitious composites.